PELATIHAN BUDIDAYA RUMPUT LAUT Eucheuma Spinosum PADA MASYAKARAT PESISIR PULAU LEMUKUTAN - Warsidah, Warsidah; Ashari, Asri Mulya (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
One fishery commodity that has economic value in trade both nationally and internationally is seaweed. Euchema spinosum belongs to the class of red seaweed (Rhodophyceae) which has great health benefits, because it contains high alginate, carrageenan and fiber, which are very good for digestion and are widely used in the textile, cosmetics, and other industries. E. spinosum also has several very important biological activities such as antioxidants.Lemukutan Island is a group of islands in the West Kalimantan region with the main livelihood of the population is fishing and farming. E. spinosum naturally grows a lot in the waters of Lemukutan Island. The potential for seaweed development in the area is very large, because in addition to the waters being far from urban or industrial activities so that a well-conditioned aquatic environment is very suitable as a seaweed cultivation center, this area is also shaded and protected so that it is not so affected by high waves from high seas.This activity aims to improve fishermen's skills while increasing productivity so that it can have an effect on improving the welfare of the farmers. The training was attended by 30 participants who are fish fishermen and seaweed farmers. The cultivation method applied in community service activities at this time is the floating netting method, using bamboo and a net at the bottom of the kerambah so that it protects the seaweed from predators such as fish and turtles. E. spinosum which is cultivated by the community in various ways, such as long line, off-bottom cages, is very risky to the threat of predators and being dragged by currents so that it has the potential to reduce the productivity of seaweed